2014
DOI: 10.1007/s13277-014-2966-x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of free rhodium (II) citrate and rhodium (II) citrate-loaded maghemite nanoparticles on mice bearing breast cancer: a systemic toxicity assay

Abstract: Breast cancer is one of the most prevalent cancer types among women. The use of magnetic fluids for specific delivery of drugs represents an attractive platform for chemotherapy. In our previous studies, it was demonstrated that maghemite nanoparticles coated with rhodium (II) citrate (Magh-Rh2Cit) induced in vitro cytotoxicity and in vivo antitumor activity, followed by intratumoral administration in breast carcinoma cells. In this study, our aim was to follow intravenous treatment to evaluate the systemic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…Otherwise, after the adsorption of ligands, the complexation of NPs' surface by carboxylic moieties of RhCit took place. Besides, some -COOH moieties remained solution-oriented, as free ionizable groups, providing the negative superficial charge and increasing the colloidal stability of Mag-RhCit NPs through electrostatic interparticle repulsion [7,23,24].…”
Section: Characterization Of Magnetic Fluid Magh-rhcit and Physical-cmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, after the adsorption of ligands, the complexation of NPs' surface by carboxylic moieties of RhCit took place. Besides, some -COOH moieties remained solution-oriented, as free ionizable groups, providing the negative superficial charge and increasing the colloidal stability of Mag-RhCit NPs through electrostatic interparticle repulsion [7,23,24].…”
Section: Characterization Of Magnetic Fluid Magh-rhcit and Physical-cmentioning
confidence: 99%
“…Previous studies with maghemite NPs and maghemite NPs functionalized with rhodium (II) citrate (Magh-RhCit) showed progress and great potential for chemotherapeutic treatment [7,[20][21][22][23][24]. However, as yet there are no studies related to the identification of the protein corona of this NP nor about its interaction in cells of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…I have already reported 13 cases of patients with cancer who have improved impressively only with the citric acid treatment that they have received, considering that they are literally cured, including this patient with medullary thyroid cancer [1], patients with peritoneal mesothelioma [4] myeloid leukemia [5], Hürthle thyroid tumor [6], endocrine hepatic tumor [7], esophageal cancer [8], multiple myeloma [9], glioblastoma multiforme [10], pancreatic cancer [11] Non Hodgkin lymphoma [12] bladder cancer [13], breast cancer [14] and a patient with multiple myeloma remitted only in 10 days with the treatment of citric acid that she received [15]; also, the fact that citric acid [citrate] is effective as a cancer treatment is demonstrated in laboratory animals [16]; but this case reported in this article is very relevant, the survival rate of an endocrine neoplasia type 2B was overcome more than 8 years only with the treatment of citric acid that the patient received.…”
Section: Textmentioning
confidence: 99%
“…Current studies with maghemite nanoparticles, an iron oxide compound, have demonstrated in vitro and in vivo specific cytotoxic action for target cells, and these results have indicated this nanoparticle as a promising option for drug delivery (Manikandan et al 2018;Chaves et al 2017;Magro et al 2018). Maghemite nanoparticles associated with rhodium citrate (MRC) have showed colloidal stability and antitumor activity in breast cancer cells (Carneiro et al 2011;Peixoto et al 2015;Chaves et al 2015;da Silva Nunes et al 2013;Rocha et al 2017).…”
Section: Introductionmentioning
confidence: 99%